School quality beyond test scores: The role of schools in shaping educational outcomes - Annalisa Loviglio (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2023)
I study how schools impact student performance and educational attainment throughout secondary education, and show that school quality cannot be easily captured by any type of rankings because students with differing characteristics and abilities benefit from different school inputs. To do so, I estimate a dynamic structural model of cognitive skills accumulation and schooling decision using rich administrative data from middle schools in Barcelona. I then simulate the outcomes that each student would have achieved in every school in the sample. Notably, the school environment has a crucial impact on the educational attainment of students from less advantaged family background and low-ability students who are at greater risk of leaving school. Moreover, the schools that would yield the highest final test scores for these students - provided they do not drop out - are not the ones that would maximize their likelihood of graduating and enrolling in further education. The results suggest that evaluating and comparing schools using only standardized assessments is insufficient for serving the needs of disadvantaged students, who require schools that enhance educational attainment rather than just test scores.
Keywords: I20; J24; C35; 330; School Value-Added; Educational Choices; Educational Attainment; Retention